Study of copper-aluminium high temperature die-attach material with different aluminium weight percentage /Shiu Kai Ping - Shiu , Kai Ping (2017)
High temperature die attach material has excellent corrosion resistance, good ductility, good electrical volume resistivity. Therefore, die attach materials have been introduced for electronic packaging. Nanoparticles have high surface energies and was developed for the use at high operational temperature. There are a lot of type of materials have been developed to prepare nanopaste which is very costly. Besides, electrical characteristic also been another issue. Through this study, Cu and Al nanoparticles were introduced in order to synthesize nanopaste by varying the aluminium percentage at 20%, 40%, 60% and 80%. CuO compound was found in the nanopaste indicated the presence of oxidation process. The use of organic additives was controlled during sintering process. The nanopaste were sintered at 380°C in order to study electrical, physical properties through scanning electron microscope and X-ray diffraction thermal characteristic. The dwell time was set at 30 minutes while for the ramp rate was set at 5°C/min respectively. AlCu, AlCu3, and Al3Cu2 were found in Cu-Al nanopaste through XRD peaks. The solid state diffusion exhibited strong absorption peak in XRD diffractogram. The melting point of copper and aluminium nanoparticles showed 196±1°C and 224±1°C respectively. The Cu20-Al80 nanopaste sample showed the lowest melting point compared to others. The electrical properties increased gradually with the increasing of aluminium weight percent content. Cu20-Al80 die attach nanopaste showed 1 × 104 (ohm-cm)-1 with the highest electrical conductivity value obtained. Formation of bigger grains and structures were viewed in the nanopaste samples in which aluminium content increased from 20% to 80%. Incomplete coalescence of particles were observed due to the aggregation of nanopaste which occurred during the nanopaste sintering process. The nanopaste sample showed promising electrical conductivity results for high aluminium content sample and therefore, aluminium proved to be a good metal.